Lifestyle Changes and Student Associations North Sumatra Who is Learning at Unimal (Case Study of Students of The Faculty Of Social And Political Sciencesa - Reza Reza; Fauzi Fauzi (Malikussaleh Social and Political Reviews, 2022)
Developments in all fields that are happening now, either directly or indirectly, require the community to be able to adapt to various forms of change and renewal. One of the people who have experienced the impact of the changes are immigrant students (nomads). An immigrant student is someone who is in the process of gaining knowledge or someone who continues his education to higher education, to another area for a long period of time or a certain period of time. In such conditions, students will usually mingle with various students from other regions. The environment that affects humans varies greatly, both in type and nature. Likewise, the variety of environments like this often affects human treatment of the environment itself. The purpose of this study was to describe the factors that influence changes in the lifestyle and socialization of North Sumatran students and the impact of changes in the lifestyles and associations of North Sumatran students. This research is a qualitative research that uses a descriptive approach method by describing the phenomena accurately regarding the facts found in the field. The research data were obtained through interviews, observations, and documentation and to complement the results of the research the authors also used a literature review. The data that has been obtained are analyzed descriptively and draw conclusions. The results of this study indicate that the lifestyle changes that occur in North Sumatra students are caused by several factors, including environmental factors, desire factors, peer factors, economic factors, and experience factors. Then, there are several impacts of lifestyle and social changes, namely the impact of language style, the impact of food style, the impact of dress style, and the impact of hanging out culture style and the impact of independent living.